THE URGENCY OF CHILD FRIENDLY SCHOOLS (CFS) IN ARABIC LANGUAGE LEARNING IN MADRASAH (ISLAMIC SCHOOL) - Nasarudin, Nasarudin; Nurjannah, Nurjannah; Sardi, Janudin; Hunainah, Hunainah; Hasaniyah, Nur; Fitriani, Fitriani (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Child-friendly school (CFS) is important in Arabic language learning because it creates a madrasah environment that supports learners' physical, emotional, social, and cognitive development, motivates, enables effective learning, and develops their creativity. This study aims to find out the importance of the concept of a child-friendly school for teachers and learners in Arabic language learning in madrasas. This study uses library research. The results of this study show that CFS helps Arabic language teachers develop their teaching strategies for creating more enjoyable Arabic language learning and helps teachers instill character education and inclusive education with the principle of equality. And CFS helps learners develop their own creativity so that they are more motivated to learn Arabic and develop their social skills.